Incidence of and Risk Factors for Developing Idiopathic Macular Hole Among a Diverse Group of Patients Throughout the United States - Ali, Ferhina S; Stein, Joshua D; Blachley, Taylor S; Ackley, Sarah; Stewart, Jay M (JAMA ophthalmology, 2017)
Idiopathic macular holes (MHs) are a cause of decreased vision among older Americans. A better understanding of risk factors for MH may help clarify the pathophysiologic factors of MH and identify potential new avenues for preventing and treating idiopathic MHs. To determine the incidence of and risk factors associated with the development of idiopathic MH requiring surgical repair with vitrectomy among a large group of managed care plan beneficiaries throughout the United States. A retrospective, longitudinal cohort study was conducted of all beneficiaries 40 years or older who were continuously enrolled for 3 or more years in a nationwide US managed care network between January 1, 2001, and December 31, 2012, who had 2 or more visits to an eye care professional. The managed care network was queried starting in 2009, and data analysis was conducted from December 1, 2014, to August 15, 2016. Development of idiopathic MH requiring surgical repair with vitrectomy. Of the 659 357 enrollees who met inclusion criteria (391 674 females and 267 683 males; mean [SD] age, 56.2 [9.2] years), 144 (0.02%) developed an MH requiring vitrectomy. After adjusting for confounding factors, females had a 64% increased risk of developing MH compared with males (adjusted hazard ratio, 1.64; 95% CI, 1.11-2.43; P = .01), with the effect of sex varying across ages. Compared with white participants, Asian-American enrollees had a 177% increased risk of developing MH (adjusted hazard ratio, 2.77; 95% CI, 1.27-6.02; P = .01). In this large cohort, sex was confirmed to be associated with developing an MH requiring vitrectomy; the effect varies across ages differently for females vs males. These differences may be the basis for the underlying pathophysiologic factors contributing to the development of MH.